Buddhism as Teaching of the “Axial Age” in the Work of Alexander Men - Sergei A. Nizhnikov; Hong Phuong Le Thi (RUDN Journal of Philosophy, 2022)
The article analyzes the interpretation of Fr. Alexander Men (1935-1990) of Buddhism as teaching of the “Axial Age”. It is based on his seven-volume work “History of Religion: In Search of the Way, Truth and Life” (1970-1983). First defines the methodology used by Fr. Alexander, which is comparative and hermeneutic in nature. At the same time, he proceeds from a theistic-Christian value position, which, nevertheless, allows him respectfully treats other religious-philosophical traditions. The originality of the author’s interpretation of Buddhism is determined, both its adequate features and one-sided, set by the value orientation. The concepts of transcendence and transcendent are differentiated, which allows conducting a comparative analysis of Buddhism and Christianity, assessments given by Fr. Alexander. The denial of the transcendent in Buddhism does not mean the absence of transcendence, especially in understanding the status of nirvana, which is defined purely apophatically. In the Indian worldview, he finds five essential principles that make Buddhism and Christianity related, despite all the difference in their positions: apophaticism, denial of the highest value of earthly goods, recognition of the high dignity of personal asceticism in spiritual life, the concept of “karma” as retribution (it is the aspect of retribution that is emphasized), the idea of salvation-liberation as the main goal of religion. These principles, in his opinion, “constitute a strong bridge connecting Eastern religious experience with the Gospel”. The work of A. Men contributes to the expansion of the cultural horizon, liberation from both nationalist and Eurocentric points of view, contributes to the development of a dialogue that is so necessary right now. It is noted that the “Axial Age” concept by K. Jaspers as a whole allows avoiding one-sided assessments, revealing the common source of all axial teachings, which can be defined as “a breakthrough to the transcendent”.